Good Faith under English Law: Evolution or revolution? - Jackson, Shy (2020)
The doctrine of good faith is not part of the general English law of contract and has a very limited role in the legal framework that applies to commercial relationships, including construction contracts. That position however has been slowly changing and this paper examines how the concept of good faith has been developing in English law and the legal basis on which it has been introduced, including the recent acceptance by the English courts of the concept of relational contracts. This is relevant in particular to construction law because there has been a growing emphasis in the UK on the use of collaborative contracts (such as partnering and alliancing contracts), which seek to put more emphasis on the wider relationship between the parties and not just the strict legal obligations expressly provided for in the contract. This paper therefore also looks at whether the changing approach to good faith can support the use of collaborative contracts but recognizing that applying such principles, in general, provides limited guidance and this paper, therefore, uses several factual scenarios to test the application of the principles and examine what their actual impact may be and would it result in any different outcomes.